Different Effects of Progressive Resistance Exercise and Knee Strengthening Exercise on Increasing Functional Capabilities in Case Knee Osteoarthritis in Paccerakkang Health Center Area - Lestari, Virny Dwiya; Durahim, Darwis; Amalia, Nur Ilma (Media Kesehatan Politeknik Kesehatan Makassar, 2022)
Knee osteoarthritis is a degenerative disease that occurs due to the aging process that attacks the knee joint. Knee OA is characterized by the erosion of joint cartilage and the formation of new bone on the joint surface. Symptoms that occur are Morning Sickness, Start Pain, Stiffness, and pain when supporting or walking, causing functional impairment of the knee. This study aims to determine the difference in the effect of Progressive Resistance Exercise and Knee Strengthening Exercise on functional ability in patients with knee osteoarthritis. The research is Quasi Experiment while the approach used is Two Group Pre Test-Post Test Design. The study population was taken from all patients with knee OA in the Paccerakg Health Center Makassar, South Sulawesi. Samples were taken by means of Accidental Sampling, totaling 16 people and divided into two groups, namely treatment group 1 with 8 people and treatment group 2 with 8 people. The data obtained were first tested using Shapiro-Wil and the results of the pre-test value of treatment group 1 were 0.922 >α 0.05 and post-test value was 0.336 >α 0.05, treatment group 2 pre-test was 0.781 >α 0 .05 and post test 0.845 >α 0.05. The data is said to be normal if p> 0.05. Then tested with Paired Simple T-test. The results of the study in treatment group 1 were 0.007 (p<0.05) and treatment group 2 was 0.001 (p<0.05), which means that there is a difference in the effect of Progressive Resistance Exercise and Knee Strengthening Exercise interventions on functional ability in patients with knee osteoarthritis.